Los talleres de asertividad y el mejoramiento del clima organizacional con enfoque humanístico-cognitivo, en la i.e. n° 1733 - mi mundo maravilloso - Ramírez Tejada, Janny Petronila (2016)
The completion of this research was aimed so that the development of assertive workshops based on cognitive-humanistic approach influences the improvement of the organizational climate of the Educational Institution No 1733 "My Wonderful World" Trujillo. For its implementation was counted with a sample population comprised of all educational stakeholders (administrators, faculty, staff and service personnel as well as practitioners), which in total were seventeen (17) The methodology that was used was quasi-experimental by the sample size and working with humans in the dependent variable has much emotional and attitudinal weight, so that a single group pre and post test was formed with an active methodology in which observation and dialogue and practical means to promote communication and interaction between all the participants before, during and at the end of each workshop, as well as in the spaces between the workshop and workshop. The results allow us to conclude that assertive workshops that were developed have improved the institutional environment, for better provision can be seen to work, identification with the institution, the higher level of responsibility, freedom and autonomy to work as well as a communication more democratic and open to receive and give feedback towards improving and beginning work positively recognizing the work, effort and contributions that are given, so I'll take proven our hypothesis.